(untitled) (Eurasian Research Bulletin, 2025)
Monitoring the depth of anesthesia is a key component of modern anesthesia care aimed at optimizing anesthetic dosing and minimizing the risk of both under- and overanesthesia. This article reviews the role of objective monitoring of the depth of anesthesia in reducing the incidence of postoperative complications, including cognitive dysfunction, delirium, cardiorespiratory complications, and increased mortality. Accurate titration of anesthetics according to neurophysiological parameters helps avoid hypnotic overdose and hypoanesthesia , thereby reducing the level of systemic stress, inflammatory reactions, and the risk of perioperative hypotension. And the use of monitoring the depth of anesthesia helps to reduce the time of awakening and accelerate postoperative rehabilitation, especially in elderly patients and those with comorbidities. The introduction of objective methods for assessing the patient’s anesthetic status is an effective strategy for increasing the safety of surgical interventions and improving clinical outcomes.